China's livestreaming industry: platforms, politics, and precarity. (November 2019) - Cunningham, Stuart; Craig, David; Lv, Junyi
This article examines conditions placing China's livestreamers as central focal points in the increasing tensions between the cultural politics and economic ambitions of digital China. Framed by concerns around 'platformization', this research uses a creator-centric critical media industries studies perspective. Chinese livestreamers enjoy a greater degree of opportunity than their Western counterparts, including competing gameplay platforms that vie for premier gameplayers who can dictate their own terms. Decades-old cultural policies fostered underlying conditions that advantage female streamers engaging in gendered performativity to appeal to lonely rich men. Livestreamers ride marketing imperatives directing consumers to cross-integrated e-commerce platforms that fuel China's emerging consumption culture. But livestreamers engage in 'edge ball' violations of Chinese norms that make them subject to an ever-increasing level of state regulatory restraint, signaling the return of ideology designed to mold online expression and behavior.